Implementasi Sistem Informasi Geografis Berbasis Web untuk Mitigasi Bencana Alam Kabupaten Bandung - Arief Ginanjar; Bintang Rizqia; Febby Juwita Hizriani; Radinda Putri Salsabila; Dieka Septiani Safitri (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
Bandung Regency is one of the regions in West Java Province that is highly vulnerable tonatural disasters, particularly floods, landslides, and earthquakes. Limited access to disasterinformation often makes it difficult for the public and related stakeholders to obtainaccurate and timely spatial information to support disaster mitigation efforts. This studyaims to implement a web-based Geographic Information System (GIS) for mapping disasterlocations and supporting disaster mitigation in Bandung Regency. The research employedan engineering research approach using the Agile Development methodology, whichincludes problem identification, data collection, system design, implementation, testing,and evaluation. The developed system integrates spatial and attribute data and presentsthem through an interactive digital map. The results indicate that the system is capable ofproviding information on disaster locations, risk levels, evacuation shelters, criticalfacilities, logistics distribution, and route navigation to the nearest location. Furthermore,the system provides different access levels for administrators and general users, enablingstructured data management and efficient information dissemination. The implementationof the web-based GIS is expected to support decision-making, improve public access todisaster information, and enhance community preparedness for disaster mitigation inBandung Regency.